Dynamic heterogeneity influences the leader-follower dynamics during epithelial wound closure - Vishwakarma, Medhavi; Spatz, Joachim P. (Philosophical transactions. Series B, Biological sciences, 2020)
Cells of epithelial tissue proliferate and pack together to attain an eventual density homeostasis. As the cell density increases, spatial distribution of velocity and force show striking similarit...